Hubungan Asupan Serat dan Lemak Total dengan Kadar Kolesterol Total pada Anggota Polisi Polres Rembang - Putri, Nadya Istiara; , Ririn Yuliati S.Si.T., M.Si; , Elida Soviana, S.Gz., M.Gizi (2016)
Introduction: The increase of total cholesterol level might cause some diseases, like hypertension and heart disease. Factors related to the increase of total cholesterol level were divided into two, they were variable factors (diet, nutritional status, physical activities, food intake like fiber and total fat) and fixed factors (age, sex, and genetic factors). The average of total cholesterol level of police officers of Rembang was ≥200 mg/dL. Objective: The objective of this study is to know the relation between fiber and total fat intake with total cholesterol level of police officers of Rembang. Research Methods: This is a observational method with cross-sectional approach. The subject of the study was 64 people, concerning inclusion criteria and exclusion criteria. Data collection method of fiber and total fat intake was by using semi-quantitative food frequency questionaire and data collection method of total cholesterol level in blood was by using Cholesterol Oxidase-Peroxidase Aminoantipyrine Phenol (CHOD-PAP). Data analysis was by using person product moment. Result of the Study: The subject of the research had total fat intake more than 89%, fiber intake more than 85,93%, and normal total cholesterol level, that was 54,68%. Conclusion: Statistics test resulted that there was relation between total fat intake and total cholesterol level (p=0,007) and there was not relation between fiber intake and total cholesterol level (p=0,141). Keywords: fiber intake, total fat intake, total cholesterol level. Bibliography: 63 : 2000-2014